Pathogenesis of Children’s Allergic Diseases: Refocusing the Role of the Gut Microbiota - Hu, Tingting; Dong, Yinmiao; Yang, Chenghao; Zhao, Mingyi; He, Qingnan (Frontiers in Physiology, 2021)
Allergic diseases comprise a genetically heterogeneous cluster of immunologically mediated diseases, including asthma, food allergy (FA), allergic rhinitis (AR) and eczema, that have become major worldwide health problems. Over the past few decades, the spread of allergic diseases has displayed an increasing trend, and it has been reported that 22% of 1.39 billion people in 30 countries have a type of allergic disease. Undoubtedly, allergic diseases, which can be chronic, with significant morbidity, mortality and dynamic progression, impose major economic burdens on society and families; thus, exploring the cause of allergic diseases and reducing their prevalence is a top priority. Recently, it has been reported that the gastrointestinal (GI) microbiota can provide vital signals for the development, function, and regulation of the immune system, and the above-mentioned contributions make the GI microbiota a key player in allergic diseases. Notably, the GI microbiota is highly influenced by the mode of delivery, infant diet, environment, antibiotic use and so on. Specifically, changes in the environment can result in the dysbiosis of the GI microbiota. The proper function of the GI microbiota depends on a stable cellular composition which in the case of the human microbiota consists mainly of bacteria. Large shifts in the ratio between these phyla or the expansion of new bacterial groups lead to a disease-promoting imbalance, which is often referred to as dysbiosis. And the dysbiosis can lead to alterations of the composition of the microbiota and subsequent changes in metabolism. Further, the GI microbiota can affect the physiological characteristics of the human host and modulate the immune response of the host. The objectives of this review are to evaluate the development of the GI microbiota, the main drivers of the colonization of the GI tract, and the potential role of the GI microbiota in allergic diseases and provide a theoretical basis as well as molecular strategies for clinical practice.